2015
DOI: 10.1007/s10096-015-2437-3
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of the relationship between antibiotic use and extended-spectrum beta-lactamase resistance in Enterobacteriaceae in a French hospital: a time series analysis

Abstract: The influence of hospital use of antibiotics other than cephalosporins and fluoroquinolones on extended-spectrum beta-lactamase (ESBL) resistance among Enterobacteriaceae is poorly known. Our objective was to explore the association between ESBL and hospital use of various classes of antibacterial agents. The relationship between monthly use of 19 classes of antibacterial agents and incidence of nosocomial ESBL-producing Enterobacteriaceae in a French hospital was studied between 2007 and 2013. Five antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Ecological studies were reported as retrospective ( n = 19); prospective ( n = 1) and unclear ( n = 8) in terms of study design. Studies were conducted in Germany, 21 , 22 , 25 , 32 , 37 France, 18 , 20 , 28 , 36 , 38 Scotland, 24 , 29 , 30 England, 39 Northern Ireland, 12 , 13 Romania, 15 , 19 Switzerland, 34 , 35 Greece, 23 Hungary, 33 Norway, 14 Slovenia, 16 Spain 27 and Serbia, 31 while a further study included data from four countries in Europe. 26 Where reported, capacity ranged from 11 bed to 3500 bed hospital settings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ecological studies were reported as retrospective ( n = 19); prospective ( n = 1) and unclear ( n = 8) in terms of study design. Studies were conducted in Germany, 21 , 22 , 25 , 32 , 37 France, 18 , 20 , 28 , 36 , 38 Scotland, 24 , 29 , 30 England, 39 Northern Ireland, 12 , 13 Romania, 15 , 19 Switzerland, 34 , 35 Greece, 23 Hungary, 33 Norway, 14 Slovenia, 16 Spain 27 and Serbia, 31 while a further study included data from four countries in Europe. 26 Where reported, capacity ranged from 11 bed to 3500 bed hospital settings.…”
Section: Resultsmentioning
confidence: 99%
“…Measures included limiting use of antibiotics, 24 , 31 , 39 the use of alcohol hand rub, 13 , 21 , 22 , 24–26 , 29 compliance audits, 21 , 22 , 26 , 29 and screening of patients with resistant pathogens. 13 , 21 , 24 , 26 , 29 , 30 , 35 , 36 , 26 , 32 Practices varied in a single study 26 that included data from five study sites in France, Hungary, Spain and Northern Ireland. Thirteen ecological studies 12 , 14–20 , 27 , 28 , 33 , 37 , 38 did not explicitly present information about measures to control AMR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potentially adverse consequences of increased prescriptions of cephalosporins rather than oral penicillin and amoxicillin are sufficiently demonstrated for the outpatient sector in our view, especially with regard to antibiotic-associated Clostridium difficile infections (24)(25)(26)(27). Data for selection of gram-negative bacteria that are extended-spectrum beta-lactamase (ESBL)-positive or otherwise resistent to cephalosporins are less certain but still plausible (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…However, broadspectrum antibiotic treatment must be used with caution, as the evidence for a direct association between antibiotics consumption and the emergence of multi-drug-resistant organisms (MDROs) cannot be neglected (12,13). Infections related to these bacteria are associated with high rate of inappropriate antibiotic treatment and worse outcomes (14).…”
Section: Introductionmentioning
confidence: 99%